Overcoming social segregation in health care in Latin America. Issue 9974 (28th March 2015) - Cotlear, Daniel; Gómez-Dantés, Octavio; Knaul, Felicia; Atun, Rifat; Barreto, Ivana C H C; Cetrángolo, Oscar; Cueto, Marcos; Francke, Pedro; Frenz, Patricia; Guerrero, Ramiro; Lozano, Rafael; Marten, Robert; et al.
Summary: Latin America continues to segregate different social groups into separate health-system segments, including two separate public sector blocks: a well resourced social security for salaried workers and their families and a Ministry of Health serving poor and vulnerable people with low standards of quality and needing a frequently impoverishing payment at point of service. This segregation shows Latin America's longstanding economic and social inequality, cemented by an economic framework that predicted that economic growth would lead to rapid formalisation of the economy. Today, the institutional setup that organises the social segregation in health care is perceived, despite improved life expectancy and other advances, as a barrier to fulfilling the right to health, embodied in the legislation of many Latin American countries. This Series paper outlines four phases in the history of Latin American countries that explain the roots of segmentation in health care and describe three paths taken by countries seeking to overcome it: unification of the funds used to finance both social security and Ministry of Health services (one public payer); free choice of provider or insurer; and expansion of services to poor people and the non-salaried population by making explicit the health-care benefits to which all citizens are entitled.